Liposarcoma in clownfish, Amphiprion ocellaris Cuvier, produced in indoor aquaculture - G Sharon; D Benharroch; L Kachko; N Reis-Hevlin; D Zilberg (John Wiley & Sons Ltd, 2025)
Clownfish, Amphiprion ocellaris Cuvier, produced and grown in an experimental indoor aquaculture facility, presented with lipomatous tumours. A total of 14 affected fish were examined. Based on the total number of fish at the aquaculture facility at the time of outbreak of this pathology, the scope of the incident is estimated to be 1 of 300 fish. The tumours were characterized by the presence of mature adipocytes of variable sizes, lipoblasts and by an invasive behaviour, which affected internal organs, muscle, central nervous system and, in one case, an eye. Detailed macroscopic and histopathological features are presented. The suggested diagnosis is that of a well-differentiated liposarcoma, a diagnosis so far never applied to fish. The limited outbreak of the neoplasm lasted a few months in 2011 and did not recur. Possible factors leading to this phenomenon, notably the metastasis, are discussed.